Using realistic evaluation to evaluate ‘Forest School’ with young people aged 14-16 with special educational needs. - Southall, Laura (2014)
This study aims to evaluate a Scandinavian approach to outdoor learning, which is used in the UK. The approach, known as ‘Forest School’ involves children and young people spending regular time in natural woodland working on practical projects. Forest School promotes a child-led ethos, so children are encouraged to choose their own activities (Forest School Association, 2013).